Investigation into methane hydrate reformation in water-dominated bubbly flow. (1st March 2020) - Chen, Yuchuan; Gong, Jing; Shi, Bohui; Yao, Haiyuan; Liu, Yang; Fu, Shunkang; Song, Shangfei; Lv, Xiaofang; Wu, Haihao; Lou, Xia
Highlights: Flow stability of hydrate slurry during the reformation process was poor compared to the first formation process. Hydrate memory effect was confirmed at the micro-level in the flow system. The prediction model of pressure drop for hydrate slurry flow was proposed. Evolution of flow patterns during the hydrate first formation/reformation process was summarized. Abstract: Hydrate reformation may lead to production line blockage in the development of natural gas hydrate reservoirs. However, few studies have focused on the flow characteristics and plugging risks during the hydrate reformation process. Therefore, experiments on hydrate reformation were carried out in a high-pressure flow loop. The hydrate induction time and formation subcooling approached for the first hydrate formation and reformation. The pressure and temperature of the first formation and reformation onset fell in a subcooling band (2.0 ± 0.5 °C). Furthermore, the flow stability of hydrate slurry for the reformation process was relatively poor compared with the first formation. Hydrate particles aggregated more violently during the reformation process when the initial flow rate was 1160 kg∙h −1 . Moreover, the hydrate memory effect at the microlevel could be confirmed from two aspects, including an increasing number of methane microbubbles (MMBs) after hydrate dissociation and a shorter time required for the decrease in the number of MMBs during the reformation process. Then, the flow pattern evolutions were summarized for different experimental conditions, and the minimum flow rate of hydrate slurry with the stable flow ability could be predicted using the classical correlation. Finally, a prediction model was developed for predicting the pressure drop in hydrate slurry flow, which considered the hydraulic, particle-aggregation, and hydrate–liquid friction effects. The findings of this work provided an insight into the behavior of methane hydrate reformation in water-dominated bubbly flow, which is an advancing research topic in the field of development of natural gas hydrate reservoirs.